Development of leaf-adhesive pesticide nanocapsules with pH-responsive release to enhance retention time on crop leaves and improve utilization efficiency. Issue 3 (17th December 2020) - Chen, Hongyan; Zhi, Heng; Liang, Jie; Yu, Manli; Cui, Bo; Zhao, Xiang; Sun, Changjiao; Wang, Yan; Cui, Haixin; Zeng, Zhanghua
Abstract : Leaf-adhesive pesticide nanocapsules improve retention time on crop leaves and utilization efficiency of pest control. Abstract : Pesticides play a very important role in pest control and plant protection. However, they can be limited by a tendency to cause ecological system damage due to significant losses into the environment. To increase pesticide utilization efficiency, we developed highly leaf-adhesive avermectin nanocapsules (Av-pH-cat@CS) with pH-responsive controlled release properties. The Av-pH-cat@CS nanocapsules displayed good thermal stability and photostability in response to UV light irradiation. The Av-pH-cat@CS nanocapsules could be disrupted at low pH and they exhibited excellent controlled release in response to pH, which improved the release of avermectins. In addition, the Av-pH-cat@CS nanocapsules were highly adhesive to crop leaves as a result of strong hydrogen bonding, which prolonged the retention time on crop leaves. The Av-pH-cat@CS nanocapsules with pH-responsive release and strong leaf adhesion improved the control efficacy and enhanced the utilization efficiency. Our findings offer a promising approach to prolonging pesticide duration on crop leaves and improving the utilization efficiency.